The Implementation of Student Worksheets (LKM) on Relations and Functions through Website-based guided-inquiry approach student worksheet - Netriwati, Netriwati; Busmayaril, Busmayaril (Desimal: Jurnal Matematika, 2020)
Student Worksheet is a learning media that can be used as a guide for students and lecturers in the teaching and learning process. The developed product of this research is a website-based guided-inquiry approach student worksheet. The purpose of this study is to improve students’ learning outcomes and motivation in learning mathematics. This research employed the pre-experimental method with one-group pretest-posttest design. The small-scale testing obtained an average score of 3.1 which is included in the interesting category. The large-scale testing obtained an average score of 3.26 which is included in the very interesting category. The website-based guided-inquiry approach student worksheet obtained an average score of 0.48 which is included in the medium category for its effectiveness. It can be concluded that the website-based guided-inquiry approach student worksheet is feasible and very interesting to be used in increasing student motivation and learning outcomes for better learning in Basic Mathematics course.